Schweres Schweben: Qualitäten der gravitas in Pina Bauschs Orpheus und Eurydike - Diagne, Mariama (transcript, 2019)
In »heavy floating«, the author develops a figure of thought that traces and re-contextualizes floating people in European dance and cultural history.